The Relationship Between Diet and the Incidence of Chronic Energy Deficiency in Pregnant Women in the Working Area of Kawangu Health Center, East Sumba District - Tamar, Maria Magdalena Dembi; Nur, Marselinus Laga; Talahatu, Anna Henny (Faculty of Public Health, Nusa Cendana University, 2024)
Chronic Energy Deficiency (CED) is a condition where a mother experiences a prolonged and continuous lack of food intake (chronic), leading to health problems. The primary factor contributing to the risk of CED in pregnant women is insufficient food consumption. This study aims to examine the relationship between dietary patterns and the occurrence of CED among pregnant women in the working area of Kawangu Public Health Center, East Sumba Regency. The research method used was analytic observation with a case-control design. The study population consisted of 40 cases and 260 controls, with a sample size of 60 pregnant women (30 cases and 30 controls). Sampling was conducted using simple random sampling, and bivariate analysis was performed using the Chi-Square test. The results showed a significant relationship between dietary patterns and the occurrence of CED in pregnant women. Pregnant women with poor dietary patterns had a lower risk of experiencing CED (p=0.000, OR=0.091). Additionally, inadequate meal frequency was also associated with CED (p=0.000, OR=0.026), as was insufficient energy intake (p=0.000, OR=0.014). However, variables such as food type and protein intake did not show a significant relationship with CED. This study recommends that pregnant women receive health education through prenatal classes to improve dietary quality, ensuring that their energy, carbohydrate, protein, vitamin, and mineral needs are adequately met.